Трансмодалізація оповіді в романі (на матеріалі роману Ірен Неміровскі «Собаки та Вовки») - Корніенко, І. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the phenomenon of transgression of narration in the novel. Taking the novel «The Dogs and the Wolves» by Irène Nemirovsky we analyze the «théâtralisation» of the prose narrative and its features. The regularities and particularities we have found prove the possibility of using the theatrical elements in the texts by Irène Nemirovsky because of her interest to the theatrical aesthetic of «l’entre-deux-guerres».